Evaluasi Penggunaan Aplikasi E-Learning Mentari UNPAM Menggunakan Metode SUS - Danil Yudhistira Setiawan; Dhelwa Efriya Salsabilla (CV. Multi Kreasi Media, 2025)
In this case, this study is conducted to see the level of usability of the Mentari UNPAM e-learning application with the System Usability Scale (SUS) method. As more and more people embrace virtual learning, the quality of a user interface and a user experience becomes an integral component in gauging an e-learning system’s effectiveness relative to ease of use, efficiency, and overall user satisfaction (usability). This method, SUS, was chosen due to its quantitative nature, simplicity, and common use as a global yardstick in empirical investigations of information systems and e-learning. Respondents in this study are active student users of the Mentari UNPAM platform. Data were collected from a 10-item SUS questionnaire and analyzed to obtain the average SUS score as a reference for system user acceptance. This indicates that the average SUS score of the Mentari UNPAM application lies in the category of above average/good (if > 68) and below average (if < 68) based on the standard interpretation of SUS. These results show that even with active use of the system, several areas need to be developed: learnability, the consistency of the interface, and the coupling of functions. The implications of this study recommend the improvement of the e-learning system through improvement of the user interface, training of users, and evaluation.